Yu Linzhu alleviates primary ovarian insufficiency in a rat model by improving proliferation and energy metabolism of granulosa cells through hif1α/cx43 pathway - Xin Ruan; Pengxu Wang; Maolin Wei; Qingqing Yang; Xiaoying Dong (BMC, 2024)
Abstract Background Yu Linzhu (YLZ) is a classical Chinese traditional formula, which has been used for more than 600 years to regulate menstruation to help pregnancy. However, the mechanism of modern scientific action of YLZ needs to be further studied. Methods Thirty SD female rats were divided into three groups to prepare the blank serum and drug-containing serum, and then using UHPLC-QE-MS to identify the ingredients of YLZ and its drug-containing serum. Twenty-four SD female rats were divided into four groups, except the control group, 4-vinylcyclohexene dicycloxide (VCD) was intraperitoneally injected to establish a primary ovarian insufficiency (POI) model of all groups. Using vaginal smear to show that the estrous cycle of rats was disturbed after modeling, indicates that the POI model was successfully established. The ELISA test was used to measure the follicle-stimulating hormone (FSH), estradiol (E2), and anti-Mullerian hormone (AMH) levels in the serum of rats. HE stain was used to assess the morphology of ovarian tissue. The localization and relative expression levels of CX43 protein were detected by tissue immunofluorescence. Primary ovarian granulosa cells (GCs) were identified by cellular immunofluorescence. CCK8 was used to screen time and concentration of drug-containing serum and evaluate the proliferation effect of YLZ on VCD-induced GCs. ATP kit and Seahorse XFe24 were used to detect energy production and real-time glycolytic metabolism rate of GCs. mRNA and protein expression levels of HIF1α, CX43, PEK, LDH, HK1 were detected by RT-PCR and WB. Results UHPLC-QE-MS found 1702 ingredients of YLZ and 80 constituents migrating to blood. YLZ reduced the FSH while increasing the AMH and E2 levels. In ovarian tissues, YLZ improved ovarian morphology, follicle development, and the relative expression of CX43. In vitro studies, we found that YLZ increased the proliferative activity of GCs, ATP levels, glycolytic metabolic rate, HIF1α, CX43, PEK, HK1, LDH mRNA, and protein levels. Conclusions The study indicated that YLZ increased the proliferation and glycolytic energy metabolism of GCs to improve follicular development further alleviating ovarian function.